Nutrigenomics and proteomics in health and disease : food factors and gene interactions - Mine, Yoshinori; Miyashita, Kazuo; Shahidi, Fereidoon , 1951- (Functional food science and technology series, 2009)
Nutrigenomics and Proteomics in Health and Disease: Food Factors and Gene Interactions aims to compile the current science based upon nutrigenomics and proteomics in food and health. Coverage includes many important nutraceuticals (food factors) and their impact on gene interaction and health.